Kandinsky’s fragile art: a multidisciplinary investigation of four early reverse glass paintings (1911–1914) by Wassily Kandinsky - Simon Steger; Diana Oesterle; Simone Bretz; Lisa Frenzel; Heike Stege; Iris Winkelmeyer; Oliver Hahn; Gisela Geiger (Heritage Science, 2019)
Abstract This work highlights the rediscovery of the technique of reverse glass painting by the artists of the “Blaue Reiter” collective in the early 20th-century and focusses particularly on the role of Wassily Kandinsky (1866–1944). Kandinsky created more than 70 reverse paintings on glass and showed several of them in exhibitions together with paintings on canvas and cardboard, implying a coequal importance of these techniques. Four of his early (1911–1914) reverse glass paintings (Auferstehung, Allerheiligen II, Rudern, Apokalyptischer Reiter II) were selected for investigation and their iconography, painting techniques and painting materials were examined. Two paintings were executed on so-called cathedral glass, revealing a “hammered surface”, whereas Kandinsky used a corrugated glass panel for Rudern. A multi-analytical, non-invasive approach [X-ray fluorescence (XRF), diffuse reflectance infrared Fourier transform spectroscopy (DRIFTS), VIS spectroscopy (VIS), Raman spectroscopy] was taken to identify the pigments and classify the binding media. The results reveal a broad palette of materials. Several pigments like lead white, zinc white, strontium yellow, Prussian blue, viridian, cadmium yellow, ultramarine blue, cinnabar and carbon black were found in most of the four paintings. The use of the rare synthetic organic pigments PR60 and PB52 is discussed. In two works of art, cadmium carbonate is associated with cadmium yellow. The identification of aluminium foil along with tin foils in Rudern indicates an early use of this material for reverse glass paintings.